Online learning readiness, online learning performance, and academic achievement in an English language course among undergraduates during an ODL semester - Md Yusof, Mimihayu; Jaapar, Wan Effa; Ishak, Nurhamizah (UiTM Cawangan Johor, 2021)
Online Distance Learning (ODL) has now been broadly implemented worldwide at almost all education levels due to the Covid-19 pandemic, though its effectiveness varies. This study looks at the online learning readiness, online learning performance, and academic achievement in an English Language subject among undergraduates in UiTM Melaka, Jasin Campus. Data on online learning readiness was collected through a questionnaire on a sample of 104 Bachelor of Computer Science and Bachelor in Plantation Technology and Management semester three students, at the beginning of the semester However, only 76 students answered the online questionnaire within the two weeks' time given (response rate =73.08). Meanwhile, data on online learning performance and academic achievement were retrieved from English lecturers who were teaching the sample. It was found that 1) both online learning readiness and online learning performance are positively correlated and predict academic achievement in an English language course conducted online, and 2) Bachelor in Computer Science students performed better in their online learning compared to their peers in Bachelor in Plantation Technology and Management. Overall, this study contributes empirical data regarding learning readiness, online learning performance, and academic achievement in English Language subjects among undergraduates during an ODL semester in a local setting. Another implication is online learning literacy must be mastered by university students nowadays to cope with the fast development of the online learning industry.